Aligning Assessments with Competencies using Keyphrase Extraction - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 2014)
Current engineering education programs aim at consistency in terms of alignment among the components of the educational system; competencies, teaching activities and assessments. Alignment requires a methodology to align the components and discover the gaps to help the faculty with their teaching activities. The current alignment methodologies are majorly manual and hence there is a need for automated principled methodology to align the educational components. In this paper, we propose an automated alignment method based on keyphrase extraction technique and Porter's alignment model. In particular we focus on aligning assessments with competencies to discover the consistency between them. We applied our methodology on a course from Information Systems Management undergraduate curriculum program. Using the competencies and the assessments designed under this course, this paper shows how our method enables educationists to measure the alignment of competencies and assessments.